Analisis Perbedaan GDP, Government Expenditures, Governance Index, Teledensity, Subsoil Asset, dan FDI Inflow Growth - Wibowo, Danny (Widya Mandala Surabaya Catholic University, 2012)
The purpose .of this study is obtain empirical evidence on differences gross Domestic product (GDP), government expenditure, governance index, teledensity, Subsoil asset, and foreign direct investment (FDI) inflow growth in state tax havens. Type of research is quantitative and the type of data in this research is secondary data. Data collection technique in this study used technical documentation. The document is the source of the data used to complete the study either in the form of written sources, films, pictures (photos), and monumental works, all of which provide information for research process. The results showed no difference level of GDP, government expenditure governance index, teledensity ,subsoil assets FDI inflow growth between Tax havens countries and the n on tax havens countries.